Has_circRNA_0122683 (circ-PRKCI) relieves ferroptosis of HPAEpiCs in sepsis-induced acute lung injury by sponging miR-382-5p - Limei Yan; Xiajun Lu; Ning Wang; Peng Jia (PeerJ)
Circular ribonucleic acid (RNA) protein kinase C iota (circ-PRKCI, hsa_circRNA_0122683) has been previously reported to be involved in the development of sepsis. However, the knowledge regarding the potential role and mechanism of circ-PRKCI in sepsis-induced acute lung injury (ALI) is unclear. An in vitro cellular model of sepsis-ALI was simulated by the treatment of lipopolysaccharide (LPS) in human pulmonary alveolar epithelial cells (HPAEpiCs). The expression of circ-PRKCI in plasma samples from sepsis patients with or without ALI as well as sepsis-ALI cell model was determined by quantitative real-time PCR (qRT-PCR). The diagnostic utility of circ-PRKCI was analyzed using receiver operating characteristic (ROC) curves. The levels of iron content (Fe2+), glutathione (GSH), malondialdehyde (MDA), and reactive oxygen species (ROS) were detected using corresponding commercial kits. The assessment of cell viability and production of pro-infammatory cytokines (IL-6, IL-1β and TNF-α) was measured using Cell Counting Kit-8 (CCK-8) and enzyme-linked immunosorbent assay (ELISA). The targeting relationship between circ-PRKCI and miR-382-5p was predicted by bioinformatics analysis, and subsequently confirmed by luciferase reporter and RNA immunoprecipitation (RIP) assays. Results shows that decreased circ-PRKCI expression but increased miR-382-5p expression was observed in sepsis patients with ALI and sepsis-induced ALI cell model. The area under the curve values of ROC curves for circ-PRKCI in differentiating septic ALI patients from healthy individuals and septic non-ALI patients were 0.996 and 0.999, respectively. Functional in vitro assays revealed that enforced expression of circ-PRKCI alleviated LPS-induced ferroptosis and inflammatory response of HPAEpiCs, which were reversed by Erastin or FIN56 administration. Mechanistically, circ-PRKCI was identified as a sponge of miR-382-5p and negatively regulated miR-382-5p expression. Further rescue experiments showed that miR-382-5p overexpression could compromise the anti-ferroptosis and anti-inflammatory response effects of circ-PRKCI on LPS-induced injury of HPAEpiCs. Our study demonstrated that circ-PRKCI may be a promising biomarker for septic ALI diagnosis. circ-PRKCI inhibits ferroptosis and inflammatory response in sepsis-induced ALI by sponging miR-382-5p, indicating that the circ-PRKCI/miR-382-5p axis might be a novel therapeutic target for the treatment of sepsis-induced ALI.